ChemInform Abstract: Ytterbium Triflate Promoted Coupling of Phenols and Propiolic Acids: Synthesis of Coumarins. Issue 43 (7th October 2016) - Fiorito, Serena; Epifano, Francesco; Taddeo, Vito A.; Genovese, Salvatore
Abstract: The improved method using microwave irradiation under solvent‐free conditions allows the synthesis of coumarins from phenols or hydroxycoumarins and propiolic acid derivatives.